If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -1z = 10 Combine like terms: 3z + -1z = 2z 2z = 10 Solving 2z = 10 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '2'. z = 5 Simplifying z = 5
| 4x^2+5x=-3 | | 8-y=9 | | -3-y=-1 | | -2-y=-1 | | 6=-3(x-5) | | 63=5x^2-26x | | x-(-38)=43 | | 8n+18=360 | | 7y=39 | | 7w-15-5w=43 | | 4+x-9+x=7 | | -1=11-x+3 | | 48+d+2(30-4d)=d | | 3+5q=15-7q | | 8x^2-56x+80=0 | | x+7y=39 | | -23-4p=19-p | | 8-y-4y=-22 | | 2m-15=9m+20 | | X^2-14X+50=0 | | 9a-6=7a+1 | | -9+8w=3w-24 | | 2(x-3)=-16 | | -y+2-y+2=8 | | 4v+13=-v+13 | | 3x^2-12x-39=0 | | 10=6-4x-8 | | -6u+11=7u-28 | | 12-7n=2n+30 | | 3c+25=-35-c | | b+8=-4b+53 | | 4a-6=-38 |